REFLECTIONS ON RUSSIAN LITERATURE «THE SUN» AND «THE MOON» IN RASPUTIN’S SHORT STORY «WOMEN’S TALK» - Shi, Hongsheng (Perm Federal Research Centre Journal, 2016)
The Russian concept «sun» symbolizes the mind of the world, enlightenment, glory, justice, God, and the Moon - the dark side of nature, the spiritual aspect of light in the dark, irrational and subjective. In his story Rasputin successfully used the symbols of «the sun» and «the moon».